Dietetics students' construction of competence through assessment and placement experiences. Issue 3 (19th June 2017) - Palermo, Claire; Dart, Janeane; Begley, Andrea; Beck, Eleanor J; Bacon, Rachel; Tweedie, Judith; Mitchell, Lana; Maher, Judith; Gallegos, Danielle; Kennedy, Meredith; Kellett, Jane; Margerison, Claire; et al.
Abstract : Aim: Competency standards are widely adopted as a framework to describe standards of performance required in the workplace. Little is known, however, about how students construct competence. This qualitative study aimed to explore how dietetics students ready to graduate construct the concept of competence and the role of assessment in developing professional competence. Methods: A qualitative description was used to gather data from a convenience sample of students ready to graduate from universities with accredited dietetics programs across Australia (10 out of 15 at the time of the study). A total of 11 focus groups were conducted to explore perspectives of competence and experiences of 'competency‐based' assessment. Data were audio‐recorded, transcribed and analysed using a thematic analysis approach. Results: A total of 81 (n = 81) participants across 10 universities representing 22% of total students participated in the focus groups. Themes revealed that: (i) there is no shared understanding of competence; (ii) current work placement experiences may not reflect current standards or workforce needs; (iii) assessment approaches may not fully support the development of competence; and (iv) the competent performance of supervising dietitians/clinical educators in the workplace influences the construction of competence. Conclusions: There is a need to work towards a shared understanding of dietetic entry‐level competence in the profession. 'Work‐based' learning experiences may need to be modified to ensure students meet current competency standards. Practitioners involved in student supervision need to acknowledge the influential role they have in the development of the future workforce.